Outcome of post caesarian pregnancy in a tertiary care hospital in Udaipur, Rajasthan - Sharma, Archana; Jadeja, Harshdeep; Malhotra, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The prevalence of caesarean section has increased due to a variety of factors such as patient choice and relative safety of the procedure. However in many cases the risk involved in LSCS is still present. Methods: The present study was designed to evaluate the outcome in cases where VBAC or TOLAC were used for the second pregnancy in a previous LSCS case. The study employed a sample of 60 subjects who were equally divided in two groups who were subjected to elective cesarian and TOLAC. Results: The results showed that TOLAC did have a better outcome as compared to repeat cesarian in context of maternal and foetal factors. Conclusions: The practice of TOLAC must be tried as an alternative and can be a viable option for uncomplicated post cesarian deliveries.